Comparison of mesoporous fractal characteristics of silica-supported organocatalysts derived from bipyridine-proline and resultant effects on the catalytic asymmetric aldol performances. Issue 17 (7th April 2022) - Xu, Guangpeng; Bing, Liujie; Jia, Bingying; Bai, Shiyang; Sun, Jihong
Abstract : The relationships between the fractal evolution and catalytic behavior of the resultant catalysts were deeply explored via SAXS method and other characterizations. The applicability and reliability of fractal theory are therefore proved. Abstract : Three kinds of the bipyridine-proline chiral ligands as highly active species were successfully introduced on Zn-modified mesoporous silica nanomaterials (BMMs, MCM-41, and SBA-15) via the covalent attachment and coordination methods. Their microstructural features and physicochemical properties were extensively characterized via XRD patterns, SEM/TEM images, TGA profiles, FT-IR and UV-Vis spectra. In particular, their fractal features, the pair distance distribution function, and the Porod plots were evaluated thoroughly on the basis of the SAXS data. Meanwhile, their catalytic performances for asymmetric aldol reactions between p -nitrobenzaldehyde and cyclohexanone were evaluated. The results indicated that the bimodal mesoporous BMMs-based samples with short worm-like mesoporous channels possessed both mass and surface fractal features, whereas the MCM-41- and SBA-15-based samples with long-range ordered structures only showed surface fractal features. The influences of various reaction parameters, including the textures of the mesoporous silicas, the structures of the used chiral ligands, and the molecular volumes of aldehydes, on the catalytic activities (yield) and stereoselectivities (dr and ee) were investigated thoroughly. The results showed satisfactory activities (yields) and better stereoselectivity (dr and ee) in comparison with the homogeneous catalytic system using Z as the catalysts. In particular, the 3 rd recycle catalytic performances of the Z-immobilized heterogeneous catalysts retained high catalytic yields (around 80%) and ee values of 28%. These phenomena were well interpreted by the essential relationships between the fractal characteristics of these heterogeneous catalysts and their catalytic activities.